Automonitoramento dos recursos hídricos em lavouras orizícolas - Lorensi, Raquel Paula (2008)
To find new solutions that rationalize the use of water represents an important strategy to hydric resources management. The rice farming stick out for being one of bigest water consumers with around 12000 m³/ha per year until 120 days of cutivation. The Right permission of hydric resources for rice farming irrigation is the tool which intends to manage this water's demand. The big problem that needs to be fiscalized for permission is the quantification of real water consume in order to confer the allowed values and the ones were really used. The fiscalization of this water volume granted to farmer can happen with the implantation of a self monitoring system. This system controls an activity made by the person who is responsable for that. This study aimed for identify workable forms in order to implant a quantitative self monitoring of rice farming water. The study area included small rice farmings in the cities of Restinga Seca e Santa Maria RS, with three types of water management. The implantation of self monitoring tests was made in the water majors conductors canals and in the entry of cultivated allotment. It was established the keycurve that characterizes the structure from levels datas. With the results, it was concluded that the implantation and operation of structures are simple because they are accessible. The results are satisfatory and the incorporation of the procedures in farmers is easy.